Towards the implementation of sustainable housing in Malaysia : awareness and readiness assessment framework - Jamaludin, Mazlina; Bakar, Abu Hassan Abu (2008)

(untitled)
The concept of sustainability has become the keystone of the global dialogue about the human future in every facets of human life. However, it is still a difficult concept for many to fully understand; locally or globally. What exactly do we intend to sustain and what will that require of us? The questions arise are what hinder the stakeholders to play their parts in sustainable housing even though the concept has been introduced two decades ago, to what extent do stakeholders aware of this concept and idea, and how far they are ready to take serious parts to work cooperatively towards achieving the objectives as stipulated in Agenda 21 which the overall human settlement objective is to improve the social, economic and environmental quality of human settlements and the living and working environments of all people, in particular the urban and rural poor. This paper attempts to specifically clarify the concept of sustainable development and the relationship between sustainability and housing. It will also try to review existing papers and housing projects from different countries on the said subject. The review will be used as a base to look further into Malaysia’s situation, its implication and approach to be taken towards the stakeholders. Subsequently, this study will help to improve guideline for effective implementation of sustainable housing in Malaysia.